Arab Republic of Egypt : 2021 Article IV Consultation, Second Review Under the Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2021)
The economic and social impact of the COVID-19 pandemic over the past year has been well-managed by the authorities. Timely and prudent fiscal and monetary easing shielded the economy from the full brunt of the crisis, while alleviating the health and social impact of the shock. Sound economic policies helped deliver macroeconomic stabilization, safeguard debt sustainability, and preserve investor confidence. While growth is expected to rebound in FY2021/22, the outlook is still clouded by uncertainty related to the pandemic and the pace of vaccinations. High public debt and large gross financing needs leave Egypt vulnerable to external shocks or changes in financial market conditions for EMs. Near-term fiscal and monetary policies should thus continue to support the recovery without accumulating undue imbalances.